Distinguishing venomous jellyfish species via high resolution melting analysis - Osathanunkul, Maslin; Sawongta, Nipitpong; Sathirapongsasuti, Nuankanya; Poonsawat, Thunyaporn; Detsri, Usawadee; Aungtonya, Charatsee; Suwannapoom, Chatmongkon (Frontiers in Marine Science, 2022)
Accurate species identification is critical for highly venomous jellyfish studies particularly for evaluation of their distribution as it is important not only for understanding population dynamics but also predicting risk to locals and tourists. Hazardous jellyfish species have been determined using methods such as comparative morphology and chemistry, which are less useful and practical in some cases. A few molecular methods have been developed in aiding hazardous jellyfish species identification. However, no studies have focused on designing and developing high resolution melting (HRM) assays to distinguish jellyfish species from each other. This is despite several studies showing the potential of HRM in effectively distinguishing plants and animals. In this study, we developed an HRM method to differentiate jellyfish species in five box jellyfish families (Carukiidae, Chirodropidae, Chiropsalmidae, Chiropsellidae, and Tripedaliidae) and Physaliidae found in Thai waters. All jellyfish samples (10 species) were able to be distinguished by the HRM with 16S rRNA primers. Even closely related species in the same genus could be clearly discriminated by their melting profiles. The melting curves of the 10 species were then used as references. By comparing the normalized melting curves of twenty-two jellyfish specimens with the reference curves, the tested specimens were assigned into species. In addition, HRM results of all jellyfish specimens tested in this study were similar to those of morphological based identification by experts. This is the first attempt of using HRM analysis to determine species of jellyfish collected from Thai waters.